#BCSM and #breastcancer: Contemporary cancer‐specific online social media communities. Issue 4 (6th September 2019) - Platt, James R.; Brady, Richard R.
Abstract: Online health care communities are commonplace on social media. This report investigates the engagement and use of breast cancer‐specific hashtags: #BCSM and #breastcancer. With over 5 million Twitter impressions weekly and increased engagement around academic meetings and news releases, these communities connect a global population. Most participants are based in the USA and work in health care; however, there is also significant engagement from the general population. Improved understanding of online hashtag communities and their output will allow us to innovate and improve the utility of this popular medium for communication in breast cancer and other disease‐specific populations.